Identification of Bioactive Compounds from Pedada Fruit Extract (Sonneratia Caseolaris) to Prevent Stunting - Damayanti, Azarine Ahnafia; Diarsvitri, Wienta; Nefertiti, Eva Pravitasari; Rahayu, Indri Ngesti (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
Stunting is a problem that still cannot be resolved throughout the world, especially in Indonesia. Children who are malnourished show high levels of blood oxidative stress biomarkers as well as inhibition in growth. To understand prevention of stunting, research was conducted using pedada fruit (Sonneratia caseolaris) which is a mangrove plant taken at the Wonorejo Magrove Ecotourism, Rungkut District, Surabaya City, East Java. The results of the research were used to reveal that there are bioactive compounds in pedada fruit extract to prevent stunting. This research used One Shot Experimental Study. The variables studied used primary data from screening of phenolic and flavonoid antioxidant metabolite compounds at the FK UHT Pharmacy Laboratory and screening for Cu, Fe, Zn mineral content at the UPT East Java Nutrition Laboratory. Result: Based on the results of qualitative phytochemical screening, pedada fruit contained phytochemical compounds, namely phenolics and flavonoids. Mineral screening of pedada fruit was carried out using the Atomic Absorption Spectrophotometry (AAS) method. Pedada fruit extract contained zinc (Zn) of 1.057 mg, while copper (Cu) and iron (Fe) of 0 mg.